CBDC and cash in the euro area: Crowding out or co-circulation? - Gerhard Rösl; Franz Seitz (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2022)
Cash usage at the point-of-sale decreased perceptibly in the past years. This is mainly due to the ongoing trend towards digitalization, but there are also indications that consumers were somewhat pushed into cashless payments by government regulations and supply-side restrictions by commercial banks. Nonetheless, overall demand for euro cash remained strong and even increased relative to GDP since the financial crisis in 2008. In this process, however, we observe a supply-driven shift towards lower banknote denominations. Central banks all over the world are intensively thinking about the potential issue of a Central Bank Digital Currency as a substitute or complement to cash. Although the characteristics of a possible digital euro have become more perceptible, its fundamental design properties remain unknown. We propose a double pre-paid scheme combining central elements of TARGET Instant Payment Settlement and electronic money features enabling offline and online instant payments. The issuance of a digital euro would be neutral to total money supply as banks act only as intermediaries. Since anonymity is categorically discarded by the ECB and as cash has some special advantages from a consumer perspective, the digital euro will rather co-circulate with cash than replace it in transactions.
Keywords: E41; E51; E58; 330; Cash; banknotes; money; CBDC